Comments on ‘Short Adult Stature and Overweight Are Associated with Poor Intellectual Performance in Subjects Born Preterm’ by Lundgren et al., Hormone Research in Paediatrics 2011;75:138–145 - Sandberg, David E. (Hormone research in paediatrics, 2011)
No abstract available Copyright © 2006 S. Karger AG, Basel [PUBLICATION ABSTRACT]